Discipline of the Heart: Murajaah as a Leadership-Driven System for Sustaining 30-Juz Memorization - Choirun Nisak; Nurhafid Ishari (Managere: Indonesian Journal of Educational Management, 2025)
This study aims to analyze the application of the murajaah method in strengthening the quality of memorization of 30 juz of the Qur'an, as well as the strategic role of kiai leadership in managing the tahfidz system. The research approach used is qualitative with a case study design. Data was collected through in-depth interviews, documentation, and findings in the field, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusions drawn. The results of the study show that the implementation of murajaah runs systematically and on a scheduled basis through four main forms: individual, group, with teachers, and in front of peers. This process not only maintains the stability of memorization but also fosters discipline, confidence, and spiritual calm in students. Kiai leadership plays an important role in designing policies, directing tahfidz teachers, and motivating students through a spiritual-transformational approach. The integration between the murajaah method and kiai leadership resulted in an Islamic education management system that was oriented towards quality, religious values, and a culture of continuous learning. This research contributes to the development of the concept of value-based leadership in the management of pesantren education. It provides a practical model for strengthening tahfidz programs in similar institutions.